2021
DOI: 10.1016/j.ecns.2021.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Simulation for Last-Year Nursing Graduate Students in Times of Covid-19: A Quasi-Experimental Study

Abstract: Background: The COVID-19 pandemic has made it necessary to adapt university health-education. Virtual simulation has been proposed to be a suitable tool. Methods: A quasi-experimental study was conducted on nursing students in the final year. The virtual simulation platform vSim® was used. Improvements in knowledge, skills during simulation, satisfaction and self-confidence obtained through the training provided were analyzed, as well as satisfaction with the platform. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 30 publications
3
18
0
13
Order By: Relevance
“…Results indicated that nursing students were generally satisfied with vSim learning. This is consistent with the results of some studies that vSim positively af- fected learner satisfaction ( Foronda et al, 2020 ;Verkuyl & Hughes, 2019 ;Zaragoza-García, Ortuño-Soriano, Posada-Moreno, Sánchez-Gómez, & Raurell-Torredà, 2021 ). These results are thought to reflect the merits of vSim, which allows nursing students to conduct self-directed learning according to their own learning pace.…”
Section: Discussionsupporting
confidence: 90%
“…Results indicated that nursing students were generally satisfied with vSim learning. This is consistent with the results of some studies that vSim positively af- fected learner satisfaction ( Foronda et al, 2020 ;Verkuyl & Hughes, 2019 ;Zaragoza-García, Ortuño-Soriano, Posada-Moreno, Sánchez-Gómez, & Raurell-Torredà, 2021 ). These results are thought to reflect the merits of vSim, which allows nursing students to conduct self-directed learning according to their own learning pace.…”
Section: Discussionsupporting
confidence: 90%
“…This kind of teaching training is also worth promoting in China, especially during the epidemic; it can ensure high-quality completion of nursing teaching work and cultivate nurses with con dence and critical thinking. Our research and previous research (7,10,(13)(14)(15) indicate that vSim for nursing may be an effective supplementary teaching strategy to improve students' self-con dence in practice and knowledge.…”
Section: Homogeneity Test Of Baseline Variables Among the Two Groupssupporting
confidence: 57%
“…Three studies by Kyung-Ah Kang (13), I Zaragoza-García (15), and Yaohua Gu (10) demonstrate that vSim participation in the teaching topics helps improve students' mastery of knowledge. The knowledge test in the I Zaragoza-García study was developed by experts at Wolters Kluwer, Laerdal® Medical, and the National League for Nursing (NLN) for vSim cases (15). Yaohua Gu's research also conducted a knowledge assessment after completing ten vSim cases (10).…”
Section: Homogeneity Test Of Baseline Variables Among the Two Groupsmentioning
confidence: 99%
“…Tiene casos clínicos revisados por pares y las simulaciones se basan en maniquíes de alta fidelidad adaptados para su uso en un entorno virtual donde mide las acciones de los estudiantes en términos de riesgo bajo, moderado y alto de daño al paciente. Además, calcula una puntuación en función de las actividades de enfermería realizadas correctamente (Foronda et al, 2016;Zaragoza et al, 2021).…”
Section: Recursosunclassified